2011
DOI: 10.1186/1475-2875-10-231
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trials of artemisinin-piperaquine, dihydroartemisinin-piperaquine phosphate and artemether-lumefantrine for the treatment of multi-drug resistant falciparum malaria in Cambodia-Thailand border area

Abstract: BackgroundDrug resistance of falciparum malaria is a global problem. Sulphadoxine/pyrimethamine-resistant and mefloquine-resistant strains of falciparum malaria have spread in Southeast Asia at lightning speed in 1980s-1990s, and the Cambodia-Thailand border is one of the malaria epidemic areas with the most severe forms of multi-drug resistant falciparum malaria.MethodsArtemisinin-piperaquine (AP), dihydroartemisinin-piperaquine phosphate (DHP) and artemether-lumefantrine (AL) were used to treat 110, 55 and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
53
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 15 publications
3
53
0
1
Order By: Relevance
“…Two-day regimens of piperaquine-containing ACTs are widely used in Cambodia despite limited availability of clinical risk assessment and cardiac (9). Based on QT prolongation seen in this study, compressed regimens of dihydroartemisinin-piperaquine could be problematic given significant issues with identifying and monitoring high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-day regimens of piperaquine-containing ACTs are widely used in Cambodia despite limited availability of clinical risk assessment and cardiac (9). Based on QT prolongation seen in this study, compressed regimens of dihydroartemisinin-piperaquine could be problematic given significant issues with identifying and monitoring high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…The risk for cardiac adverse events in this population is therefore uncertain. At the time of the study, the Cambodian military frequently used 2-day treatment courses of dihydroartemisinin-piperaquine (Artekin) and other piperaquine-containing products such as artemisinin-piperaquine (Artequick) given with food to improve medication compliance (9). Given this compressed dosing period and administration with food, although understandable with respect to compliance, the contradiction of formal dosing recommendations created the need to investigate QTc interval under these modified conditions.…”
mentioning
confidence: 99%
“…In adults in Thailand, the protective efficacy of DHAPQ was 98% when DHAPQ was administered monthly and 86% when it was administered bimonthly (11). Despite extensive clinical evaluation and use of DHAPQ in Southeast Asia (12,13) and Africa (14)(15)(16), few studies have addressed pharmacokinetics of PQ in children (17)(18)(19). However, one of these studies suggested that children are underdosed with current regimens (17), which was also supported by a recent meta-analysis (20).…”
mentioning
confidence: 86%
“…Although ASϩMQ and AL treatment failures have previously been reported from Battambang and Pursat (2,13), the clinical efficacy of these regimens in the setting of DHA-PPQ resistance is not known. However, studies have suggested a lack of cross-resistance between PPQ and MQ in vitro; for example, pfmdr1 amplification is associated with decreased susceptibility to MQ but increased susceptibility to PPQ (14).…”
mentioning
confidence: 99%